Putting the brakes on transcription at damaged chromatin: Do Polycomb silencers do more than modify histones?. (1st November 2016) - Kee, Younghoon
ABSTRACT: One of the cellular responses to DNA damage is to monitor and execute temporary arrest of RNA synthesis at chromatin lesions. The Polycomb silencer BMI1 is a well-known contributor to this process. We recently described a new mode of BMI1-mediated transcription arrest at lesions that involves UBR5 E3 ligase and FACT histone chaperon.